Interplay between Plasma Turbulence and Particle Injection in 3D Global Simulations. Issue 6 (4th July 2016) - Tamain, P.; Bufferand, H.; Carbajal, L.; Marandet, Y.; Baudoin, C.; Ciraolo, G.; Colin, C.; Futtersack, R.; Galassi, D.; Ghendrih, P.; Nace, N.; Schwander, F.; et al.
Abstract: The impact of a 3D localized particle source on the edge plasma in 3D global turbulence simulations is investigated using the TOKAM3X fluid code. Results apply to advanced fueling methods such as Supersonic Molecular Beam Injection (SMBI) or pellets injection. The fueling source is imposed as a volumetric particle source in the simulations so that the physics leading to the ionization of particles and its localization are not taken into account. As already observed in experiments, the localized particle source strongly perturbs both turbulence and the large scale organization of the edge plasma. The localized increase of the pressure generated by the source drives sonic parallel flows in the plasma, leading to a poloidal redistribution of the particles on the time scale of the source duration. However, the particle deposition also drives localized transverse pressure gradients which impacts the stability of the plasma with respect to interchange processes. The resulting radial transport occurs on a sufficiently fast time scale to compete with the parallel redistribution of particles, leading to immediate radial losses of a significant proportion of the injected particles. Low Field Side (LFS) and High Field Side (HFS) injections exhibit different dynamics due to their interaction with curvature. In particular, HFS particle deposition drives an inward flux leading to differences in the particle deposition efficiency (higher for HFS than LFS). These results demonstrate the importance of taking into account plasma transport in a self‐consistent manner when investigating fueling methods. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)